Peranan Potensi Sektor Ekonomi Daerah terhadap Kelangsungan Pendapatan Asli Daerah Kabupaten Mojokerto: The Role of Potential Regional Economic Sectors in the Sustainability of Original Regional Income of Mojokerto Regency - Sari, Intan Permata (Indonesian Journal of Sustainability Policy and Technology, 2023)
The regional original income sustainability is very important for the interests of citizens and the government. This research analyzes the role of potential economic sectors that influence Mojokerto Regency's Original Regional Income (PAD). The data used is secondary data from the Regional Development Planning Agency and the Central Bureau of Statistics of Mojokerto Regency. The data analysis method used is a descriptive qualitative analysis using income ratios. In contrast, descriptive quantitative analysis uses the Location Quotient (LQ) method and multiple linear regression using the Statistical Program for Social Science (SPSS) tool to show the influence between the independent variables and dependent variables. The results of this research showed that six basic sectors are developing in Mojokerto Regency, including the transportation and communications sector; electricity, gas, and clean water sectors; building or construction sector; financial, rental, and corporate services sectors; trade, hotel, and restaurant sectors; and the services sector. Based on the results of multiple linear regression analysis, it was found that the electricity, gas, and clean water sectors; the trade, hotel, and restaurant sectors; and the transportation and communications sector did not affect PAD, while the construction/building sector; financial, rental, and corporate services sectors; and the services sector influences PAD of Mojokerto Regency. These results indicate that several sectors have important developments for the sustainability of Mojokerto's PAD. Therefore, it is recommended that the Mojokerto Regency government continue to develop these sectors, especially the construction sector; financial, rental, and corporate services sectors; and the services sector. ABSTRAK: Kelangsungan Pendapatan Asli Daerah sangat penting untuk kepentingan warga dan pemerintah. Penelitian ini bertujuan untuk menganalisis peran sektor-sektor ekonomi potensial yang berpengaruh terhadap Pendapatan Asli Daerah (PAD) Kabupaten Mojokerto. Data yang digunakan merupakan data sekunder yang diperoleh dari Badan Perencanaan Pembangunan Daerah dan Badan Pusat Statistik dan Kabupaten Mojokerto. Metode analisis data yang digunakan merupakan analisis kualitatif deskriptif dengan mengambil rasio-rasio pendapatan, sedangkan analisis kuantitatif deskriptif menggunakan metode Location Quotient (LQ) dan regresi linier berganda dengan menggunakan alat bantu Statistic Program for Social Science (SPSS) untuk menunjukkan pengaruh antara variabel bebas dan variabel terikat. Hasil penelitian ini didapatkan enam sektor basis yang berkembang di Kabupaten Mojokerto antara lain sektor pengangkutan dan komunikasi; sektor listrik, gas dan air bersih; sektor bangunan atau konstruksi; sektor keuangan, persewaan dan jasa perusahaan; sektor perdagangan, hotel dan restoran; dan sektor jasa-jasa. Berdasarkan hasil analisis regresi linier berganda dengan didapatkan sektor listrik, gas dan air bersih, sektor perdagangan, hotel dan restoran, sektor pengangkutan dan komunikasi tidak berpengaruh terhadap PAD, sedangkan sektor kontruksi/bangunan; sektor keuangan, persewaan dan jasa Perusahaan; dan sektor jasa-jasa berpengaruh terhadap PAD Kabupaten Mojokerto. Hasil ini mengindikasikan bahwa beberapa sektor memiliki perkembangan yang penting untuk kelangsungan PAD Mojokerto. Oleh karena itu, disarankan agar pemerintah Kabupaten Mojokerto untuk terus mengembangkan sektor-sektor tersebut, khususnya sektor kontruksi/bangunan; sektor keuangan, persewaan dan jasa Perusahaan; dan sektor jasa-jasa.